A Monolithic Force‐Sensitive 3D Microgripper Fabricated on the Tip of an Optical Fiber Using 2‐Photon Polymerization. Issue 16 (26th February 2018) - Power, Maura; Thompson, Alex J.; Anastasova, Salzitsa; Yang, Guang‐Zhong
Abstract: Microscale robotic devices have myriad potential applications including drug delivery, biosensing, cell manipulation, and microsurgery. In this work, a tethered, 3D, compliant grasper with an integrated force sensor is presented, the entirety of which is fabricated on the tip of an optical fiber in a single‐step process using 2‐photon polymerization. This gripper can prove useful for the interrogation of biological microstructures such as alveoli, villi, or even individual cells. The position of the passively actuated grasper is controlled via micromanipulation of the optical fiber, and the microrobotic device measures approximately 100 µm in length and breadth. The force estimation is achieved using optical interferometry: high‐dimensional spectral readings are used to train artificial neural networks to predict the axial force exerted on/by the gripper. The design, characterization, and testing of the grasper are described and its real‐time force‐sensing capability with an accuracy below 2.7% of the maximum calibrated force is demonstrated. Abstract : 2‐photon polymerization is used to produce a tethered, 3D, compliant grasper with integrated force sensing, the entirety of which is fabricated on the tip of an optical fiber. Optical interferometry combined with artificial neural networks facilitate real‐time force estimation during manipulation tasks. Such grippers can prove useful for the interrogation of biological microstructures such as alveoli, villi, or even individual cells.